The Essence of the Public Interest Principle in Petroleum Mining According to the Constitution - I Gede Janitra Rad Winatha; Putri, Meliana (Focus Journal : Law Review, 2024)
Indonesia is a country that has abundant natural resources, but Indonesia faces challenges in regulating petroleum mining so that it can always improve people's welfare. Therefore, this research will focus on examining the actual role of the state in implementing the principle of public interest in the field of petroleum mining as mandated by the 1945 Constitution of the Republic of Indonesia. This principle of public interest is intended to ensure that petroleum resources are considered strategic. by the state can be managed for the greatest prosperity of the people so that it is in line with the objectives of the constitution, namely justice, expediency and legal certainty. To achieve this, the state must be able to provide parameters regarding the extent to which the regulation concerns the public interest so that it can be used as a guide in interpreting state control over natural resources and ensuring their utilization for the greatest prosperity of the people. stated in the law. constitution. This principle has actually been tested and enforced through various legal frameworks and Constitutional Court decisions, thereby further emphasizing the role of the state in prioritizing community welfare in petroleum mining activities.